2014
DOI: 10.1007/s13244-014-0311-y
|View full text |Cite
|
Sign up to set email alerts
|

MDCT of acute subaxial cervical spine trauma: a mechanism-based approach

Abstract: Injuries to the spinal column are common and road traffic accidents are the commonest cause. Subaxial cervical spine (C3–C7) trauma encompasses a wide spectrum of osseous and ligamentous injuries, in addition to being frequently associated with neurological injury. Multidetector computed tomography (MDCT) is routinely performed to evaluate acute cervical spine trauma, very often as first-line imaging. MDCT provides an insight into the injury morphology, which in turn reflects the mechanics of injury. This arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 35 publications
(46 reference statements)
3
19
0
Order By: Relevance
“…Images were analyzed using a DICOM System, part of the PACS (picture archiving and communication system) Aurora 3 (version 1.5.5, Pixeon Medical System). 13,17,21 We excluded patients with incomplete clinical and radiological data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Images were analyzed using a DICOM System, part of the PACS (picture archiving and communication system) Aurora 3 (version 1.5.5, Pixeon Medical System). 13,17,21 We excluded patients with incomplete clinical and radiological data.…”
Section: Methodsmentioning
confidence: 99%
“…3,4,6,7 While many studies suggested that the SLIC is reliable and safe, the morphological characterization of injuries was limited and unspecific. [10][11][12][13][14][15][16] In this context, in 2015, Vaccaro et al proposed a new classification for SCST based on CT evaluation and morphology, adopted by AOSpine, in an attempt to improve the morphological classification (Table 1). 3,[10][11][12][13][14][15][16] Given the importance of an accurate classification system to standardize treatment and compare outcomes, evaluation of the reliability and safety of this new morphological classification system is necessary.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Each category is analyzed individually and scored. A score less than or equal to three indicates conservative management while a score greater than five suggests surgical intervention [6][7][8]. Early surgery is thought to benefit patients with unstable fractures but there is no consensus on the timing or type of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…For consideration of blunt trauma affecting the sub-axial cervical spine (i.e. trauma of the cervical spine below the craniocervical junction), the reader is directed to other such dedicated reviews [1]. …”
Section: Introductionmentioning
confidence: 99%